INPUT SHAPING TECHNIQUES FOR SWAY CONTROL OF A ROTARY CRANE SYSTEM (Jurnal Teknologi (Sciences & Engineering), 2017)
This paper investigates the performance of input shaping techniques for sway control of a rotary crane system. Unlike the conventional optimal controllers, input shaping is simple to design and cost effective as it does not require feedback sensors. Several input shapers were implemented and their performances were compared which are useful for future sway control designs. A nonlinear model of the system was derived using the Lagrange’s energy equation. To investigate the performance and robustness of input shaping techniques, zero vibration (ZV), zero vibration derivative (ZVD), zero vibration derivative-derivative (ZVDD) and zero vibration derivative-derivative-derivative (ZVDDD) were proposed with a constant cable dimension. Level of reduction of the payload sway was used to assess the control performance of the shapers. Simulation and real time experimental results have shown that ZVDDD with an average sway reduction of 88% has the highest level of sway reduction and robustness to modeling errors as compared to 85%, 80% and 65% for ZVDD, ZVD and ZV respectively.